2020
DOI: 10.3390/jcm10010074
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Spinal Stenosis Inpatients Treated with Integrative Korean Medicine Treatment

Abstract: The present prospective observational study aimed to analyze the outcomes of inpatients who received integrative Korean medicine treatment in order to provide evidence on its effects on lumbar spinal stenosis (LSS). Patients with LSS who received inpatient treatment at four Korean medicine hospitals from January 2015 to December 2018 were followed up. Outcomes measured included the numeric rating scale (NRS) scores for back and leg pain, and Oswestry Disability Index (ODI). Changes in outcomes at admission, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The prevalence of degenerative lumbar spinal stenosis (DLSS) in the population increases with age, and as the population ages, the health problems associated with DLSS are becoming increasingly severe [2][3][4]18]. Patients with first-episode DLSS should first try multimodal rehabilitation that combines lifestyle changes, exercise, and physical therapy, as well as conservative treatments such as nonsteroidal and opioid medications and epidural injections, and about 30-50% of patients who have mild to moderate pain and walking ability will improve [19][20][21][22][23]. Patients who have failed conservative treatment for 3-6 months or who have severe lower back pain and walking disorders should be treated surgically [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of degenerative lumbar spinal stenosis (DLSS) in the population increases with age, and as the population ages, the health problems associated with DLSS are becoming increasingly severe [2][3][4]18]. Patients with first-episode DLSS should first try multimodal rehabilitation that combines lifestyle changes, exercise, and physical therapy, as well as conservative treatments such as nonsteroidal and opioid medications and epidural injections, and about 30-50% of patients who have mild to moderate pain and walking ability will improve [19][20][21][22][23]. Patients who have failed conservative treatment for 3-6 months or who have severe lower back pain and walking disorders should be treated surgically [24][25].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Pharmacopuncture for stenosis tends to be combined with acupuncture and Chuna manual therapy. In one study, when integrated Korean medical treatment was administered to patients with LSS, 93.6% of patients admitted to the clinic received pharmacopuncture and 14.0% received bee venom acupuncture, 38 illustrating the active practice of pharmacopuncture for stenosis. Another retrospective chart review with a follow-up survey also reported the efficacy of multimodal Korean medicine therapy, including Hwangryunhaedoktang pharmacopuncture in patients with LSS.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) age 50-80 years; (2) pain or discomfort in the low back or lower extremity for at least 3 months; (3) diagnosis of LSS on computed tomography or magnetic resonance imaging; (4) Visual Analog Scale (VAS) score of 4-7; (5) no difficulty in language, concentration, and expression; (6) availability for follow-up evaluations during the trial period; and (7) voluntary participation. The exclusion criteria were as follows: (1) history of hypersensitivity reactions or side effects to acupuncture treatment; (2) need for severe surgical treatment for cauda equina syndrome or neurological symptoms of sensory or motor paralysis; (3) spinal surgery before the trial; (4) a lumbar epidural nerve block within 3 months of the trial; (5) neurodegenerative diseases or neuromuscular scoliosis; (6) abnormal liver function, defined as alanine aminotransferase and aspartate aminotransferase levels three times higher than the reference range; (7) abnormal renal function test results (blood urea nitrogen level 7-23 mg/dL, creatinine level 0.6-1.3 mg/dL); (8) or current neurological or psychologically significant disease; (9) pregnant or lactating women and those who have planned pregnancy or refuse appropriate contraceptive options; (10) anticoagulant medication; (11) artificial pacemaker; and (12) deemed inappropriate to participate in the clinical trial by the clinical trial director.…”
Section: Participantsmentioning
confidence: 99%
“…5,6 The indications for surgery vary widely, but in adult patients aged >65 years, spinal stenosis is the most common indication for low back surgery. 7 However, radiographic findings and clinical symptoms of spinal stenosis may not necessarily correlate, and thus, surgical procedures should be cautiously decided. 8 On the other hand, conservative treatments encompass pharmacological management with nonsteroidal anti-inflammatory medications, epidural steroid injections, physical therapy, and regular exercise.…”
Section: Introductionmentioning
confidence: 99%